2017
DOI: 10.25175/jrd/2017/v36/i2/116391
|View full text |Cite
|
Sign up to set email alerts
|

Rural Employment Diversification in North East India: An Analysis

Abstract: Situational analysis of rural non-farm employment (RNFE) space in the North East India shows presence of severe regional variation. It also exhibits very high magnitude of feminisation and casualisation of employment in the construction sub-sector of RNFE. Although, the gender gap in the RNFE space in this region has virtually disappeared, gender deprivation is very much present and disquieting. This is reflected when women workers are increasingly pushed to undertake supportive, residual, casual and non-remun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The motives behind employment diversification have been classified broadly into "push" and "pull" factors (Drall and Mandal, 2020;Haggblade et al, 2010;Jatav and Sen, 2013;Alobo Loison, 2015;Nakajima et al, 2018;Panda, 2017;Ranjan, 2009;Unni, 1996). Under a dynamic agricultural situation, favourable production and consumption linkages expand the growth of lucrative non-farm jobs which acts as a pull factor for diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The motives behind employment diversification have been classified broadly into "push" and "pull" factors (Drall and Mandal, 2020;Haggblade et al, 2010;Jatav and Sen, 2013;Alobo Loison, 2015;Nakajima et al, 2018;Panda, 2017;Ranjan, 2009;Unni, 1996). Under a dynamic agricultural situation, favourable production and consumption linkages expand the growth of lucrative non-farm jobs which acts as a pull factor for diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Matsumoto et al (2006) found an increase in the income of farm households by 9.1% in Kenya, 14.5% in Uganda and 12.5% in Ethiopia due to diversification. Works by Jatav and Sen (2013), Lanjouw and Shariff (2004), Misra (2014) and Panda (2017) established that education and vocational training act as a facilitator for rural employment diversification in India. Another notable determinant is the size of land ownership.…”
Section: Rural Non-farm Employment In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Mulberry planting, manuring, irrigation, weeding, mulberry leaf picking, mulberry leaf transportation and leaf storage, women frequently involved in these sericulture operations. They are also involved in leaf-cutting, feeding, worm spacing, bed cleaning, mounting, cocoon harvesting, and disinfectant during silkworm rearing, and women were also involved in post-harvesting activities of cocoons like silk reeling, silk spinning, silk twisting, silk weaving etc., Some are still involved in decision-making [7,10,11,12,13]. So the study aim is to analyse the problems faced by women in these activities involved in production and marketing of mulberry silk.…”
Section: Introductionmentioning
confidence: 99%